A Comprehensive Bibliometric Analysis Of The Internationalization Of Higher Education And Student Mobility: Investigating Scholarly Trends And Dynamics - Dr. Ratnam Mishra, Sanchita Chaudhary (Journal of Informatics Education and Research, 2025)
Purpose: This study examines the trends, evolution and future direction of international student mobility and the internationalization of higher education using bibliometric analysis. Research Design: This study analyzes scholarly publications from 1995 to 2023 using the SCOPUS database. This study applies bibliometric method including co-authorship mapping, performance analysis, and thematic clustering to identify core areas of research using systematic keyword searches. Findings: Five main research themes emerge from the analysis: (i) factors facilitating internationalization, (ii) integrating globalization in higher education institutions, (iii) equity, diversity, and inclusion, (iv) cultural adaptation of international students, and (v) obstacles and difficulties faced by foreign students. The findings show a notable increase interest in this field. Originality: This study offers a systematic and data-driven overview of internationalization in higher education, offering insights in this area, has evolved over the past almost three decades. By identifying gaps, bringing disparate research themes together, and guiding institutional and policy-level strategies for improving global education. It adds too the body of knowledge in academia. The bibliometric approach further demonstrates its usefulness in mapping knowledge structures in a field of academia that is becoming more dynamic and complex.